2013
DOI: 10.1002/anie.201307205
|View full text |Cite
|
Sign up to set email alerts
|

New Endeavors in Gold Catalysis—Size Matters

Abstract: International audienceGolden times: Recent breakthroughs in gold-catalyzed transformations using nanosized homogeneous gold catalysts are highlighted. These catalysts have activities and stabilities comparable to (or even surpassing) heterogeneous catalysts. Well-defined, ligand-supported gold clusters turned out to be active in homogeneous catalysis, a catalyst concept which holds potential for future studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In gold catalysis, many efforts have been devoted in the rational design of ligands based on large backbones. 357 It was envisioned that size effects could influence both the metal center and the activated substrates and consequently, the outcome of the process. 19 To achieve this aim, there are a few strategies to follow such as (i) the use of reversible interactions to prepare the ligand scaffold, (ii) based on multiple catalyst- substrate interactions, (iii) encapsulation of the gold-based catalyst, and (iv) using supramolecular regulation of the activity of the catalytic system.…”
Section: Sterically Hindered Gold Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In gold catalysis, many efforts have been devoted in the rational design of ligands based on large backbones. 357 It was envisioned that size effects could influence both the metal center and the activated substrates and consequently, the outcome of the process. 19 To achieve this aim, there are a few strategies to follow such as (i) the use of reversible interactions to prepare the ligand scaffold, (ii) based on multiple catalyst- substrate interactions, (iii) encapsulation of the gold-based catalyst, and (iv) using supramolecular regulation of the activity of the catalytic system.…”
Section: Sterically Hindered Gold Complexesmentioning
confidence: 99%
“…In gold catalysis, many efforts have been devoted in the rational design of ligands based on large backbones . It was envisioned that size effects could influence both the metal center and the activated substrates and consequently, the outcome of the process .…”
Section: Sophisticated Gold Catalystsmentioning
confidence: 99%
“…2 The properties of nanoparticles strongly depend on their size, shape, crystallinity and structure, which determine their specic applications. 3 In particular, metal nanoparticles with high-index facet surfaces exhibit fascinating surface-enhanced and catalytic properties compared to spherical ones. 4 It was recently shown that Au nanoparticles with high-index facets exhibit facet-dependent catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tunability and mechanistic understanding for heterogeneous catalysts are more difficult compared to homogeneous catalysts due to their structural complexity. In recent years, heterogeneous catalysts are being “downsized” to the point that they are becoming “molecular” in order to achieve higher activity and/or better atom economy, while homogeneous catalysts are being “heterogenized” on surfaces. For the latter, anchoring strategies are necessary, including electropolymerization and anchoring groups such as carboxylates and phosphonates. Synthetic procedures to introduce and to deprotect these groups are often challenging and are required to be tolerated by the molecules where they are being introduced.…”
mentioning
confidence: 99%